Modulating Patellofemoral Joint Stress Through Targeted Neuromuscular Training in Runners: A Systematic Review and Meta-Analysis - I Gusti Made Baskara Teragnya Mahaputra; Bagus Bayu Pradnyana; Made Dwi Puja Setiawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Patellofemoral pain syndrome remains a highly prevalent running-related injury, characterized by retropatellar pain exacerbated by knee flexion. While multifactorial, biomechanical imbalances and proximal neuromuscular deficits are primary contributors. This systematic review and meta-analysis evaluated the efficacy of targeted neuromuscular training and gait retraining on pain, functional capacity, and biomechanical parameters in runners with patellofemoral pain syndrome. Methods: A systematic search and analysis were conducted, incorporating nine randomized controlled trials. Inclusion criteria focused on adult runners diagnosed with patellofemoral pain syndrome undergoing neuromuscular exercise or gait retraining compared to control or standard care. Primary outcomes included self-reported pain and functional status. Standardized Mean Differences with 95 percent confidence intervals were calculated using an inverse-variance random-effects model. Results: Nine randomized controlled trials involving robust sample sizes were analyzed. The pooled meta-analysis for pain reduction demonstrated a statistically significant large effect size favoring targeted neuromuscular and gait retraining interventions (Standardized Mean Difference = -1.38, 95 percent confidence interval [-1.85, -0.91], p less than 0.001). Functional outcomes also showed significant improvement in the intervention groups (Standardized Mean Difference = 1.51, 95 percent confidence interval [1.02, 2.00], p less than 0.001). Biomechanical analyses indicated significant modulations in hip kinematics, notably reduced peak hip adduction. Conclusion: Targeted neuromuscular training and gait retraining significantly reduced pain and improved lower extremity function in runners. These interventions successfully modulated patellofemoral joint stress through enhanced proximal control and altered strike mechanics.